2019
DOI: 10.3310/pgfar07100
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment with sertraline for adults with depressive symptoms in primary care: the PANDA research programme including RCT

Abstract: Background Despite a growing number of prescriptions for antidepressants (over 70 million in 2018), there is uncertainty about when people with depression might benefit from antidepressant medication and concern that antidepressants are prescribed unnecessarily. Objectives The main objective of the PANDA (What are the indications for Prescribing ANtiDepressAnts that will lead to a clinical benefit?) research programme was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
1
7
1
Order By: Relevance
“…Additionally, this difference is comparable with the effect of some medications used to manage anxiety, such as sertraline. A United Kingdom study showed sertraline, when used for a six-week period, could reduce GAD-7 scores by (21%) [ 35 ], compared to (27.4%) in our study, albeit this difference was between the two treatment groups, rather than one group.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, this difference is comparable with the effect of some medications used to manage anxiety, such as sertraline. A United Kingdom study showed sertraline, when used for a six-week period, could reduce GAD-7 scores by (21%) [ 35 ], compared to (27.4%) in our study, albeit this difference was between the two treatment groups, rather than one group.…”
Section: Discussioncontrasting
confidence: 82%
“…For example, adding a telephone service to computerized CBT in combating anxiety yielded a reduction of 1.18 in GAD-7 scores [46]. Again, the percentage of change in GAD-7 scores in our study after providing a daily text message for 6 weeks (19.0%) is consistent with the effect of medications on anxiety symptoms; in a very large randomized controlled trial in the United Kingdom, sertraline was evidently effective in reducing GAD-7 scores by 21% after 6 weeks, and this result was described as clinically important [47].…”
Section: Principal Findingssupporting
confidence: 85%
“…Furthermore, in a previous randomized trial [ 23 ], participants received the intervention for 12 weeks compared to 6 weeks in our study, which may account for the observed differences in the effects. Another study examined the effect of sertraline, an antidepressant of the selective serotonin reuptake inhibitor class, in ameliorating depressive symptoms; this study reported only a 5% relative reduction (95% CI 7%-15%; P =.41) in the mean PHQ-9 score at week 6 [ 47 ], which is not vastly different from the apparent 2% improvement observed with our Text4Hope intervention.…”
Section: Discussionmentioning
confidence: 89%
“…The possible responses were 'I feel a lot better', 'I feel slightly better', 'I feel about the same', 'I feel slightly worse' and 'I feel a lot worse'. 33 We created a dichotomous variable: feeling worse (1) and feeling the same or better (0).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…In 2017, we recruited another PPI member, Lucy Carr, who was a former participant in a NIHR-funded trial, PANDA. 33 She was an independent member of the Trial Steering Committee and contributed, along with Paul Lanham, to the design and content of the study documentation, including patient information sheets and self-harm protocols.…”
Section: Public and Patient Involvementmentioning
confidence: 99%